Stock Implied Volatility, Stock Turnover, and the Stock-Bond Return Relation - Chris Stivers; Licheng Sun (Federal Reserve Bank of Atlanta, 2002)
The authors examine how the co-movement between daily stock and Treasury bond returns varies with stock market uncertainty. They use the lagged implied volatility from equity index options to provide an objective, observable, and dynamic measure of stock market uncertainty. The authors find that stock and bond returns tend to move substantially together during periods of lower stock market uncertainty. However, stock and bond returns tend to exhibit little relation or even a negative relation during periods of high stock market uncertainty. The authors' findings have implications for understanding joint cross-market price formation. Further, their findings imply that diversification benefits increase for portfolios of stocks and bonds during periods of high stock market uncertainty.
Keywords: 330; Stock market; Stocks; Bonds